Classical Test Theory: Measurement for Fashion Design Double Track High School Program - Irma Russanti; Eko Hariadi; Tri Rijanto (Indonesia Approach Education, 2022)
The Double Track High School Program is a program that provides the provisions of high school students in order to have competencies such as vocational students, one of which is the Fashion Design competency. Tests are needed to measure students' cognitive abilities. This research is a test that aims to obtain information on the validation of the Fashion Design cognitive test items using the classical test theory. This quantitative descriptive study uses a multiple choices test with four choices of 40 items. Participants' responses were collected through Google form for Fashion Design class of 2019 and 2018 totaling 122 respondents. The analysis technique with the strata program was analyzed using classical test theory. Based on the analysis of the cognitive validation tests of fashion design competencies Double track high school program results obtained the validation of the test uses classical test theory with a test reliability coefficient of 0.5729 for the number of tests as many as 40 questions, meaning the question items has moderate reliability. The conclusion is a test can be used for fashion design double track high school program.